2010
DOI: 10.1128/jb.00448-10
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein YbeY Is Required for Optimal Activity of the 30S Ribosomal Subunit

Abstract: The highly conserved bacterial ybeY gene is a heat shock gene whose function is not fully understood. Previously, we showed that the YbeY protein is involved in protein synthesis, as Escherichia coli mutants with ybeY deleted exhibit severe translational defects in vivo. Here we show that the in vitro activity of the translation machinery of ybeY deletion mutants is significantly lower than that of the wild type. We also show that the lower efficiency of the translation machinery is due to impaired 30S small r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…The Δ ybeY mutant is reported to have both defective 30S and 50S subunits (Davies et al, 2010; Rasouly et al, 2010). To determine whether this unique 70S ribosome quality control is mediated specifically by either the defective 30S or 50S subunit, we purified subunits from wild type and the Δ ybeY mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The Δ ybeY mutant is reported to have both defective 30S and 50S subunits (Davies et al, 2010; Rasouly et al, 2010). To determine whether this unique 70S ribosome quality control is mediated specifically by either the defective 30S or 50S subunit, we purified subunits from wild type and the Δ ybeY mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Association of Era with membranes versus association with RNA appears to be competitive (33). It should be added that the third gene of the operon, ygfG , encodes a protein homologous to E. coli YbeY, which is also thought to be involved in regulating ribosomes (77,78) and is structurally similar to certain eukaryotic metalloproteases (107). These observations suggest that UDPK plays a role in a stress-induced pathway that modulates ribosome function.…”
Section: Proteomics and Microbial Physiologymentioning
confidence: 99%
“…Previous studies indicated that YbeY is important for translation and its absence results in production of impaired 30 S ribosomal subunits because of abnormal maturation of rRNA [26][28]. Recently [29] YbeY was shown to be a metallo endoribonuclease and with several functions including rRNA maturation and 70 S ribosome quality control.…”
Section: Introductionmentioning
confidence: 99%